The WTO and environment-related international trade disputes biosecurity and ecosystem services risks - Fraser, Robert W.; Cook, David C.; Haddock-Fraser, Janet (World Scientific, 2020)
"We live in a world that is increasingly dependent on international trade in a context of substantial regional/national political tensions. Adding to this is an emerging understanding and concern about the social impact of biosecurity and ecosystem services risks associated with such trade. As the key international trade 'arbiter', the World Trade Organization (WTO) has never before faced such complexity within its decision-making remit. With increasing numbers of bilateral and regional agreements, as well as new developments emerging such as the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) initiated by multi-national corporations in 2018, the WTO needs to implement ways of reinforcing its legitimacy and enhancing its relevance. This book provides an original analysis of these linked developments and delivers a timely contribution to resolving environment-related international trade disputes. It provides a clear roadmap for improving WTO trade dispute resolution procedures so both biosecurity and ecosystem services risks are considered in evaluating the social, economic and environmental impacts of international trade proposals. In so doing, the WTO should deliver enhanced multilateral social welfare."--